Multiple spontaneous coronary artery dissections associated with intravenous daunorubicin treatment for acute myelocytic leukaemia: a case report. Issue 1 (21st December 2020) - Chien, Do Van; Hai, Pham Dang; Nhung, Le Thi; Son, Pham Truong
Abstract: Background: Multiple spontaneous coronary artery dissection (SCAD) is a rare condition which may lead to serious consequences such as sudden cardiac death, acute myocardial infarction (AMI), and acute heart failure. Case summary: In this paper, we report the case of a 57-year-old woman with acute myelocytic leukaemia who was undergoing her second phase of chemotherapy. After the first induction cycle of intravenous infusion of daunorubicin, the patient experienced chest pain, shortness of breath, and low blood pressure. The electrocardiograms revealed significant ST-elevation in the D1, aVL, and V2–V6 leads, which indicated AMI. Coronary catheterization showed spontaneous coronary dissection in the mid-left descending coronary artery and first obtuse marginal artery of the circumflex. The patient died immediately. Discussion: This is the first reported case of multiple SCAD associated with intravenous (IV) daunorubicin infusion. We also reviewed the literature and proposed the mechanism of this complication.